Splenectomy indications and outcomes among children: a retrospective study from a tertiary care center in Saudi Arabia - Alhejaili, Jood M.; AlShawa, Mohammad A.; Alharbi, Atheer H.; Alnassar, Saleh I. (International Surgery Journal, 2026)
Background: Splenectomy is a surgical procedure frequently performed on children and adolescents for several hematological indications. It is recognized as a safe and feasible procedure. However, post-splenectomy complications are recognized well in some cases. Experienced surgeons play a vital role in managing intra-operative and postoperative complications. Evaluate indications, outcomes and complications of splenectomy among children and to find out the indications for open splenectomy in the era of minimally invasive surgery in a tertiary care center. Methods: A retrospective study was conducted among 71 children (0-14) years old who underwent a splenectomy at King Faisal Specialist hospital and Research Center (KFSHRC) in Riyadh, Saudi Arabia, from 2010-2019. The study is based on electronic medical records. Data analysis was carried out using the Excel analysis tool. Results: In total, 71 pediatric participants were included in this study. 60 (84.5 %) of them underwent laparoscopic splenectomy (LS) and 11 (15%) open splenectomy (OS). For LS (35 males, 25 females), while in OS (Seven males, four females). The median age was seven years among the LS group and six among the OS group. The average hours of surgery were 2:13 Hours (LS) while 2:23 Hours (OS). The median hospital stay among LS was four and a half days and the OS group was six days. The most common immediate postoperative complication was fever. Conclusions: Laparoscopic Splenectomy has become the standard of care. LS has advantages over OS, like earlier recovery and shorter hospital stay.